1984
DOI: 10.1046/j.1468-2982.1984.0401033.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea in Cluster Headache

Abstract: The impetus to study sleep changes in a cluster population arose from a recent hypothesis that predicted the finding of sleep apnea in this disorder. It holds that cluster attacks may occur in response to oxygen desaturation. Proposed mechanisms involve impairment of carotid body activity secondary to hypothalamic-vasomotor regulatory dysfunction. Five chronic and five episodic cluster patients underwent nocturnal polysomnography, utilizing standard equipment for monitoring sleep status, cardiac activity, nasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
98
1
4

Year Published

1986
1986
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(108 citation statements)
references
References 9 publications
5
98
1
4
Order By: Relevance
“…The fi rst study was done by Kudrow et al [2] in 1984. In their study, six of 10 patients with CH who were studied presented with sleep apnea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fi rst study was done by Kudrow et al [2] in 1984. In their study, six of 10 patients with CH who were studied presented with sleep apnea.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CH is also characterized by its nocturnal periodicity. The nocturnal attacks may make up 50% to 60% of the attacks [2]. Characteristically, CH is associated with the rapid eye movement (REM) period of sleep and may sometimes occur during or at the end of this period [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In Paiva et al's [10] study, 3 patients had obstructive sleep apnea syndrome among 13 migrainous patients. Kudrow et al showed evidence of sleep apnea in 6 of 10 cluster headache patients: 4 of these patients had central apnea, and 2 obstructive apnea [9].…”
Section: Discussionmentioning
confidence: 99%
“…Dexter [8] showed that 36%-58% of patients with sleep apnea complaint of morning headache and that headache may be the presenting complaint of sleep apnea syndrome. Kudrow et al [9] found a 60% prevalence of sleep apnea among ten patients with cluster headache. Paiva et al [10] demonstrated that in several cases of adult migraine, after a polysomnographic (PSG) study, diagnosis has been changed in half of the patients and the treatment of the underlying clinical condition greatly improved the headache.…”
Section: Introductionmentioning
confidence: 97%
“…Weekend-Migräne; [6,11]). Umgekehrt können Migräneatta-cken auch direkt aus dem Schlaf heraus auftreten, wobei dabei wahrscheinlich der REM-Schlaf-Phase besondere Bedeutung zukommt (Übersicht in: [11] Möglicherweise gibt es jedoch Unterschiede zwischen der chronischen und der episodischen Form [26,42]. 3.…”
Section: Literaturübersichtunclassified